10 Wireless laser transmission technology for biomedical image information transmission. (March 2019) - Tang, YF; Zhan, WD; Hao, ZQ; Li, R
Abstract : Background: In the biomedical field, biomedical imaging and X-rays are common techniques, but there has been some damage to medical staff. Wireless laser transmission is the best technology for information transmission between the imaging detector and processing terminal. It can reduce system complexity and human injury. Methods: It is proposed that wireless laser communication technology be used for biomedical imaging. The DFB laser and EA modulator are integrated. To improve the rate of laser modulation, the modulation model is built, the coupling parameters are optimized, the electrode structure is improved, and the chirp effect is reduced. The laser modulation method is OOK, which uses the signal mixed method to fuse the multi-channel video data from the surgery. The fused data is loaded into the modulator through the driving circuit. The receiver receives and fuses the signal, then constructs the video scene of the operation site. Results: The transmission rate achieved was 2.5Gbps, BER precedes 1E-7, the transmission delay was less than 1 ms and the four-channel HD video signal was fused. Conclusions: The technology is very suitable for biomedical imaging because the wireless laser communication does not have electromagnetic radiation, promotes good real-time results and does not require laying of a cable. Acknowledgements: Supported by a project grant from Jilin Provincial Science and Technology Department (Grand No.20150204040SF).